Immunisation coverage, 2012 - Hull, Brynley P; Dey, Aditi; Menzies, Rob I; Brotherton, Julia M; McIntyre, Peter B (Communicable Diseases Intelligence, 2014)
This, the 6th annual immunisation coverage report, documents trends during 2012 for a range of standard measures derived from Australian Childhood Immunisation Register (ACIR) data, and National Human Papillomavirus (HPV) Vaccination Program Register data. These include coverage at standard age milestones and for individual vaccines included on the National Immunisation Program (NIP) and coverage in adolescents and adults. The proportion of Australian children ‘fully vaccinated’ at 12, 24 and 60 months of age was 91.7%, 92.5% and 91.2%, respectively. For vaccines available on the NIP but not assessed during 2012 for ‘fully vaccinated’ status or for eligibility for incentive payments (rotavirus and pneumococcal at 12 months and meningococcal C and varicella at 24 months) coverage varied. Although pneumococcal vaccine had similar coverage at 12 months to other vaccines, coverage was lower for rotavirus at 12 months (83.6%) and varicella at 24 months (84.4%). Although ‘fully vaccinated’ coverage at 12 months of age was lower among Indigenous children than non-Indigenous children in all jurisdictions, the extent of the difference varied, reaching a 15 percentage point differential in South Australia but only a 0.4 percentage point differential in the Northern Territory. Overall, Indigenous coverage at 24 months of age exceeded that at 12 months of age nationally and for all jurisdictions, but as receipt of varicella vaccine at 18 months is excluded from calculations, this represents delayed immunisation, with some contribution from immunisation incentives. The ‘fully vaccinated’ coverage estimates for vaccinations due by 60 months of age for Indigenous children exceeded 90% at 91% in 2012. Unlike in 2011, at 60 months of age, there was no dramatic variation in coverage between Indigenous and non-Indigenous children for individual jurisdictions. As previously documented, vaccines recommended for Indigenous children only, hepatitis A and pneumococcal vaccine, had suboptimal coverage at 60.1% and 73.1%, respectively, although there was a considerable improvement in coverage from 2011, 57.7% and 68.2% respectively. On-time receipt (before 49 months of age) of vaccines by Indigenous children at the 60-month milestone age improved substantially between 2011 (19%) and 2012 (38%) but the disparity in on-time vaccination between Indigenous and non-Indigenous children worsened at the 60-month age milestone from 2011 (from 1.8 to 5.4 percentage points) and remained the same for the 12 and 24-month age milestones. By late 2012, the percentage of children who received the 1st dose of DTPa vaccine dose at less than 8 weeks of age was greater than 50% in all but 1 jurisdiction and greater than 70% for New South Wales, the Australian Capital Territory and Tasmania. Further, by late 2012, the percentage of children who received the 4th dose of DTPa vaccine dose at less than 4 years of age was greater than 30% in 3 jurisdictions. The percentage of children whose parents officially objected to vaccination in Australia was 1.7% and this figure varied by jurisdiction. However, there is a further 2.1% of children whose parents don’t officially object but whose children have no vaccines recorded on the ACIR. Coverage data for the 3rd dose of HPV from the national HPV register in the school catch up program was similar to 2011 at 71% but was substantially lower for the catch up program for females outside school (44%–69%), although this was an improvement from 2011. Commun Dis Intell 2014;38(3):E208–E231.